Synthesis and performance evaluation of Moringa Oleifera seed coat biosorbent for carbamazepine adsorption from model wastewater - Daramola, Michael Olawale (University of Pretoria, 2025)
Dissertation (MEng (Chemical Engineering))--University of Pretoria, 2025.